2008
DOI: 10.1590/s0004-282x2008000600014
|View full text |Cite
|
Sign up to set email alerts
|

Is cold the new hot in sudden unexpected death in epilepsy? Effect of low temperature on heart rate of rats with epilepsy

Abstract: -Sudden unexpected death in epilepsy (SUDEP) is the commonest cause of seizure-related mortality in people with refractory epilepsy. Several risk factors for SUDEP are described; however, the importance of including low temperatures as risk factor for SUDEP was never explored. Based on this, the aim of this study was to evaluate the heart rate of rats with epilepsy during low temperature exposure. Our results showed that low temperature clearly increased the heart rate of rats with epilepsy. Taken together, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Exposure to low temperatures is well-established as one of the risk factors in cardiac mortality 4 , and our group reported that winter temperatures may lead to some cardiovascular abnormalities and hence SUDEP 5 . This hypothesis has been experimentally evaluated and we demonstrated that low temperatures clearly increase the heart rate of rats with epilepsy, suggesting that cold weather could be considered an important risk factor in cardiovascular abnormalities and therefore sudden cardiac death in epi-lepsy 6 . Following this reasoning, colder temperatures have been associated with an increase in vascular resistance, coronary vasospasm, blood pressure, and hemostasis 4 .…”
Section: Discussionmentioning
confidence: 95%
“…Exposure to low temperatures is well-established as one of the risk factors in cardiac mortality 4 , and our group reported that winter temperatures may lead to some cardiovascular abnormalities and hence SUDEP 5 . This hypothesis has been experimentally evaluated and we demonstrated that low temperatures clearly increase the heart rate of rats with epilepsy, suggesting that cold weather could be considered an important risk factor in cardiovascular abnormalities and therefore sudden cardiac death in epi-lepsy 6 . Following this reasoning, colder temperatures have been associated with an increase in vascular resistance, coronary vasospasm, blood pressure, and hemostasis 4 .…”
Section: Discussionmentioning
confidence: 95%
“…Many predisposing and triggering factors may coexist in SUDEP [9], including the presence of generalized tonic-clonic seizures, polytherapy with antiepileptic drugs, onset of the disease at an early age, long-term seizure disorder (over 15 years), cold climates [5,10,11], abnormalities of the cardiovascular system, central apnea, and primary brain failure related to seizures (Table 1) [12,13]. The ILAE Commission on Epidemiology identified increased frequency of generalized tonic-clonic seizures, use of polytherapy, longer duration of epilepsy, young age at the onset of the disease, gender, and symptomatic etiology as risk factors for SUDEP [14].…”
Section: Introductionmentioning
confidence: 99%
“…Em 2000, o estudo conduzido por Pope [6] resumiu os mecanismos fisiológicos de efeito das partículas finas na saúde humana. A descrição destes mecanismos de efeito aborda diversos desfechos, como doenças cardiovasculares, respiratórias, do aparelho reprodutivo, dentre outras, e surge como foco de investigação de vários autores [7,8,9,10,11] . No entanto, estudos epidemiológicos, com base na morbidade e mortalidade, também são realizados e caracterizam-se como forte instrumento para ampliar esta discussão à saúde pública [1,2] .…”
Section: Cross-over Studiesunclassified